0189 Work Productivity Loss Associated with Sleep Duration, Insomnia Severity, Sleepiness, and Snoring. (27th April 2018) - Yang, R; Hale, L; Branas, C; Perlis, M; Gallagher, R; Killgore, W; Gehrels, J; Alfonso-Miller, P; Grandner, M
Abstract: Introduction: The present study examined the relationship between sleep symptoms and work productivity in a diverse community sample. Methods: Data from the Sleep and Healthy Activity, Diet, Environment, and Socialization (SHADES) study was used, including N=1, 007 adults age 22–60. Work productivity was assessed with the validated Well-being Assessment of Productivity (WBAP), which includes items assessing impact of health, caregiving, lack of resources, coworker issues, overscheduling, supervisor issues, worries, depression/anxiety, financial stress, technical issues, and lack of training (each scored 0–2). Sleep duration was assessed using the NHANES item for typical weekday sleep and categorized as very short (≤4h) short (5-6h), normal (7-8h, reference), and long (≥9h). Other measures included the Insomnia Severity Index (none, mild, moderate/severe), Epworth Sleepiness Scale (low/high), and loud snoring (none, <1/week, 1–2/week ≥3/week). Covariates included age, sex, race/ethnicity, education, income, and work hours. Caffeine was assessed as never/rarely, occasionally, or daily. Regression analyses used sleep variables to predict WBAP score, adjusted for covariates. Secondary analyses explored individual items. Results: Lower productivity was associated with very short (B=1.31, 95%CI[0.05, 2.58], p=0.042), short (B=1.14, 95%CI[0.47, 1.80], p=0.001), and long (B=1.48, 95%CI[0.06, 2.90], p=0.04) sleep. It was also associated with both mild (B=1.94, 95%CI[1.29, 2.59], p<0.0001) and moderate-severe (B=4.06, 95%CI[3.31, 4.86], p<0.0001) insomnia and sleepiness (B=1.88, 95%CI[1.24, 2.52], p<0.0001), as well as snoring <1/week (B=1.77, 95%CI[0.84–2.67], p<0.0001), 1–2/week (B=1.51, 95%CI[0.39, 2.63], p=0.008), and ≥3/week (B=1.74, 95%CI[0.74, 2.73], p=0.001). Examining mean differences, this reflects additional relative productivity loss of 29% (very short sleep), 19% (short sleep), 24% (long sleep), 58% (mild insomnia), 107% (moderate-severe insomnia), 50% (sleepiness), and 19–34% (snoring). Conclusion: Sleep duration (both short and long), insomnia, sleepiness, and snoring were all associated with decreased work productivity. Among sleep symptoms, insomnia demonstrated the greatest impact on work productivity. Sleep should be considered an important element in workplace health. Support (If Any): The SHADES study was funded by R21ES022931.